2002
DOI: 10.1074/jbc.m208395200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Studies of Sugar Binding to Galactose Mutarotase from Lactococcus lactis

Abstract: Galactose mutarotase catalyzes the conversion of ␤-Dgalactose to ␣-D-galactose in the Leloir pathway for galactose metabolism. The high resolution x-ray structure of the dimeric enzyme from Lactococcus lactis was recently solved and shown to be topologically similar to the 18-stranded, anti-parallel ␤-motif observed for domain 5 of ␤-galactosidase. In addition to determining the overall molecular fold of galactose mutarotase, this initial investigation also provided a detailed description of the electrostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Indeed, mutarotases have been shown to turn over various sugars including D-glucose, D-fucose, D-quinovose, L-arabinose, and D-xylose (8,23,33). With the gene sequence for the human enzyme now known, it will be possible to explore both its pattern of tissue expression and subcellular location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mutarotases have been shown to turn over various sugars including D-glucose, D-fucose, D-quinovose, L-arabinose, and D-xylose (8,23,33). With the gene sequence for the human enzyme now known, it will be possible to explore both its pattern of tissue expression and subcellular location.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, regardless of the source, mutarotases tend to show a preference for galactose over glucose and have high k cat and K m values with this sugar (typically 10 4 Ϫ 10 5 s Ϫ1 and 10 Ϫ 100 mM, respectively) (23, 30 -33). The preference of these enzymes for galactose over glucose was addressed structurally with the L. lactis mutarotase and, at least in the case of this bacterial protein, is explained by the existence of nonproductive binding modes in the active site for glucose and its derivatives (33). With respect to quaternary structure, human mutarotase appears to be monomeric (10,30), whereas the L. lactis enzyme was shown to be a dimer on the basis of ultracentrifugation experiments (24).…”
mentioning
confidence: 99%
“…Although galactosemia is rare, it is a potentially lethal genetic disease with clinical manifestations, including intellectual retardation, liver dysfunction, and cataract formation, among others. At present, the high resolution x-ray crystallographic structures of three of the four enzymes in the pathway, namely galactose mutarotase, galactose-1-phosphate uridylyltransferase, and UDP-galactose 4-epimerase, are known through efforts by this laboratory (3)(4)(5)(6)(7)(8)(9). The remaining enzyme of unknown structure, galactokinase, catalyzes the second step of the pathway, the ATP-dependent conversion of ␣-D-galactose to galactose 1-phosphate.…”
mentioning
confidence: 99%
“…This pocket, which contains a glycerol-bound molecule bound in the so-called apo structure, corresponds to the active site in galactose mutarotase. Crystal structures of Lactococcus lactis galactose mutarotase bound to sugars have shown that these residues are involved in sugar binding (11,25). Site-directed mutagenesis led to the conclusion that in L. lactis galactose mutarotase, His 170 and Glu 304 play the role of catalytic acid and base, respectively (26).…”
Section: Resultsmentioning
confidence: 99%